Highly ordered functional fiber and preparation method thereof
By using tannin acid to encapsulate the core layer of MXene nanosheets and the shell layer of polyvinylpyrrolidone in the fibers, coaxial fibers are prepared by using wet spinning technology, which solves the problem of easy agglomeration and oxidation during the preparation process, and achieves efficient sensing and long life of the material.
Patent Information
- Application Number
- CN202510077114.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The prior art is difficult to maintain the dispersion and stability of MXene materials, resulting in their prone to agglomeration and oxidation during the preparation process, and their interfaces with fibers or fabrics are not well combined, resulting in the short service life of the sensing fibers or fabrics.
Coaxial fibers with core and shell are prepared by wet spinning technology. The core layer is composed of tannin-encapsulated MXene nanosheets. Through the synergistic action of physical shear and TA adhesion, the shell is polyvinylpyrrolidone, providing a spatial domain confined channel to promote the orientation arrangement of MXene and prevent oxidation.
It significantly improves the conductivity of MXene nanosheets, enhances the sensing and shielding properties of the material, extends the service life of the material, and optimizes the interface structure of the composite material, giving full play to the performance advantages of different components.
Smart Images

Figure CN119824573A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber preparation, and in particular to highly ordered functional fibers and a preparation method thereof. Background Art
[0002] With the continuous development of human civilization, people's lifestyles have also undergone tremendous changes. Textile fiber products are not just for warmth and decoration. Functional products are a new direction for the development of the fiber industry. Among them, coaxial fiber is a new type of fiber material with unique structure and excellent performance, and its application field is wide. Traditional coaxial fiber preparation technology mainly focuses on the combination of different polymers or materials to achieve specific performance requirements. However, with the rapid development of the Internet of Things, flexible electronic devices, biomedicine and other fields, the functional requirements for coaxial fibers are also getting higher and higher. For example, humidity sensing, strain response, etc.
[0003] MXene, the full name of which is two-dimensional transition metal carbon / nitride, is prepared by selectively etching the A layer in the MAX phase of a ternary layered compound. M is one or more transition metal elements (such as Ti, Sc, Zr, Nb, etc.), X represents carbon or nitrogen, A represents Al, Si, Ga, etc., and T x It represents the functional groups generated on its surface during chemical etching (such as O, F, OH, Cl, etc.). MXene materials have good mechanical properties and high electrical conductivity, and have broad application prospects in many high-tech fields.
[0004] At present, the preparation of flexible sensing fibers or fabrics using MXene mostly adopts surface functionalization modification (surface impregnation, spraying, etc.), or constructs a conductive network on the fiber surface. However, MXene sheets are easy to agglomerate, and maintaining their dispersion and stability during the preparation process is still a technical challenge; at the same time, MXene is very easy to react with water and oxygen, resulting in poor chemical stability, so that the oxidized TiO2 nucleates and grows and diffuses on the entire sheet surface, resulting in defects in the MXene nanosheet structure and functional attenuation; in addition, the weak interface bonding between MXene and fibers or fabrics makes it easy to fall off, which makes the service life of the sensing fiber or fabric short. Summary of the invention
[0005] The present invention aims to solve at least one of the above technical problems and proposes a highly ordered functional fiber and a preparation method thereof.
[0006] To achieve the above object, the first technical solution adopted by the present invention is: The highly ordered functional fibers are coaxial fibers with a core layer and a shell layer prepared by wet spinning. The core layer is tannic acid-encapsulated MXene nanosheets. The composite material obtained by self-assembly has a directional structure of stacked layers, and the shell layer is polyvinyl pyrrolidone.
[0007] Preferably, the mass ratio of tannic acid to MXene nanosheets is 1:(1-9).
[0008] Preferably, the shell layer also contains collagen.
[0009] Preferably, the mass ratio of the collagen to polyvinyl pyrrolidone is 1:(1-5). The second technical solution adopted by the present invention is: A method for preparing highly ordered functional fibers, comprising: The MXene nanosheets were dispersed in deionized water, tannic acid was added, and magnetic stirring was performed at pH 7-10 for 1-12 h to obtain a core layer spinning solution; Dissolving polyvinyl pyrrolidone in water to obtain a shell spinning solution; The core layer spinning solution and the shell layer spinning solution are used to prepare coaxial fibers by wet spinning.
[0010] Preferably, the spinning speed ratio of the core layer to the shell layer is 1:(1-5).
[0011] The metering speed ratio of the shell layer and the core layer during the wet spinning process is (1-5):1.
[0012] Preferably, the drawing speed ratio of the spinneret, the first drawing machine and the second drawing machine during the wet spinning process is 1:1:(1-5).
[0013] Preferably, the preparation method of MXene nanosheets is that Ti3AlC2 selectively etches the aluminum layer in HCl / LiF solution, ultrasonically peels off the aluminum layer, centrifuges to obtain the supernatant, and freeze-dries the supernatant.
[0014] Preferably, polyvinyl pyrrolidone and collagen are dissolved in water to obtain a shell spinning solution.
[0015] Preferably, the coagulation bath used in wet spinning is a saturated anhydrous sodium sulfate solution.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The core material of the coaxial fiber of the present invention is MXene nanosheets encapsulated by tannic acid, which has a directional structure of stacked layers under the combined effect of physical shear and TA adhesion, which significantly improves the conductivity of the MXene nanosheets, and comprehensively improves the sensing performance and shielding performance of the material. At the same time, due to the spatial confinement channel provided by the shell material, it not only promotes the directional arrangement of the MXene nanosheets, but also avoids its long-term contact with the complex environment, thereby extending the service life of the material. A stable and compatible interface network is constructed between the functional fiber core layer and the shell material provided by the present invention, which can not only optimize the interface structure inside the composite material, but also give full play to the performance advantages of different components, so that the composite material maintains excellent functionality while also taking into account good mechanical properties.
[0017] The present invention uses tannic acid to encapsulate MXene nanosheets into TA-MXene nanosheets with stable performance, thereby improving the dispersion stability of MXene nanosheets in water or other solvents and preventing them from agglomerating and settling. In addition, since TA contains a large number of hydroxyl groups, it can form multi-site hydrogen bonds with MXene, and water and oxygen will preferentially react with TA, consuming the oxidation source. Water and oxygen that reach the vicinity of Ti atoms no longer react with Ti, which can effectively prevent the oxidation of MXene. The core-shell structure of the present invention solves the problem that MXene is easily oxidized when exposed to complex environments for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a digital photo of the MXene dispersion prepared in Example 1; Figure 2 The monolayer Ti3C2T in the MXene dispersion prepared in Example 1 x Microscopic morphology of MXene nanosheets; Figure 3 The raw material Ti3AlC2 in Example 1 and the single-layer Ti3C2T in the prepared MXene dispersion x X-ray diffraction spectrum of MXene nanosheets; Figure 4 The effect diagram of the TA-MXene dispersion and the MXene dispersion prepared in Example 1 after standing for 50 days; Figure 5 The microscopic morphology of the surface (a, b) and cross section (c, d) of the Col / PVP@TA-MXene coaxial fiber prepared in Example 1; Figure 6 The small-angle diffraction patterns of the coaxial fibers prepared in Example 1 (a) and Comparative Examples 1-2 (b-c), where f is the orientation factor; Figure 7 The resistance change diagram of the coaxial fiber prepared in Example 1 and Comparative Examples 1-2; Figure 8 This is the sensing performance diagram of the coaxial fiber prepared in Example 1. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical scheme and advantages of the present invention clearer, the scheme of the present invention is further described in detail below in conjunction with embodiment.It will be appreciated by those skilled in the art that the following examples are exemplary only, and are not intended to limit the scope of the present invention.In addition, in the following description, those not indicating specific conditions in the examples are carried out according to the conditions of normal conditions or manufacturer's recommendations.Reagents used or instruments not indicating manufacturers are conventional products that can be obtained by commercial purchase.
[0020] The first embodiment of the present invention provides a highly ordered functional fiber, which is a coaxial fiber having a core layer and a shell layer prepared by wet spinning. The core layer is a composite material with a layer-by-layer stacked oriented structure obtained by self-assembly of MXene nanosheets encapsulated with tannic acid through shear flow technology, and the shell layer is polyvinyl pyrrolidone.
[0021] The functional fiber provided by the present invention adopts a space-confined structure design coated with a shell layer. The shell layer imposes a certain spatial restriction on the MXene nanosheets of the core layer. This restriction not only guides the MXene to be arranged in an orderly and directional manner, but also promotes the orderliness of its structure. At the same time, tannic acid (TA) is used to encapsulate the MXene nanosheets. Since tannic acid has adhesion properties, the interaction force between the MXene nanosheets can be significantly enhanced. Under the synergistic effect of physical shear force and TA adhesion, MXene exhibits excellent self-assembly function, so that it can spontaneously form a stacked directional structure. This stacked directional structure has a positive effect on the conductivity of the material. Its inherent mechanism is that when MXene nanosheets are stacked layer by layer in an orderly manner, the electron transmission path between them becomes more direct and efficient, reducing the scattering and obstruction of electrons during transmission. This structural optimization enables electrons to flow quickly and smoothly inside the composite material, thereby significantly improving the conductivity of the material. This improvement is crucial for the sensing, shielding and other properties of the material, and can make the material more sensitive and efficient in receiving and transmitting signals.
[0022] It should be noted that the physical shear force referred to above refers to the physical shearing achieved by giving different spinning speeds and different drawing speeds through the coaxial spinning needle during the wet spinning stage, thereby realizing the layer-by-layer stacking and self-assembly of MXene. Specifically, the metering speed ratio of the shell layer and the core layer during the wet spinning process is (1-5):1, and the drawing speed ratio of the spinneret, the first drawing machine, and the second drawing machine is 1:1:(1-5).
[0023] The present invention proposes an innovative interface engineering strategy. Since TA has good interface affinity, its unique molecular structure can establish an effective interface bond between the layers of the composite material. Specifically, the multiple phenolic hydroxyl groups in the tannic acid molecule can form hydrogen bonds or chemical bonds with different components in the composite material. This chemical interaction significantly improves the interfacial compatibility between the two phases. The mechanism is that TA constructs a stable and compatible interface network inside the composite material through chemical bonding and hydrogen bonding, which can not only optimize the interface structure inside the composite material, but also give full play to the performance advantages of different components, so that the composite material maintains excellent functionality while also taking into account good mechanical properties.
[0024] The functional fiber of the present invention adopts a shell coating design, which cleverly solves the problem that the surface functional particles are easy to fall off and oxidize when using traditional surface dipping, spraying and other methods. This not only avoids the long-term contact of functional particles with complex environments, but also prevents the loss of core functional particles during the preparation process. These advantages work together on the material, further extending the service life of the material, so that it can maintain excellent performance and stability in various application scenarios.
[0025] The present invention encapsulates MXene into TA-MXene nanosheets with stable performance by introducing tannic acid (TA) with a polyhydroxy structure. Since TA contains a large number of hydroxyl groups, it can form multi-site hydrogen bonds with MXene. Water and oxygen will preferentially react with TA to consume the oxidation source. The water and oxygen that reach the vicinity of Ti atoms will no longer react with Ti, thereby preventing the oxidation of MXene.
[0026] In some preferred embodiments, the mass ratio of tannic acid to MXene nanosheets is 1:(1-9).
[0027] In some preferred embodiments, in order to improve the biocompatibility of the functional fiber, collagen is also added to the shell layer, so that the functional fiber of the present invention can be used to prepare medical devices such as wound dressings and tissue engineering scaffolds.
[0028] The mass ratio of the collagen to polyvinyl pyrrolidone is 1:(1-5).
[0029] The second embodiment of the present invention provides a method for preparing highly antioxidant functional fibers, comprising: dispersing MXene nanosheets in deionized water, adding tannic acid, and magnetically stirring at pH 8 to obtain a core spinning solution; dissolving polyvinyl pyrrolidone in water to obtain a shell spinning solution; and preparing the core spinning solution and the shell spinning solution into coaxial fibers by a wet spinning method.
[0030] The intensity of the physical shear force in the wet spinning process can be controlled by different injection speeds, and the action time lasts throughout the entire wet spinning stage, including spinning, coagulation, drawing and other processes.
[0031] For the embodiments of the present invention, the size of the coaxial spinning needle used in the wet spinning stage is a size commonly used in the art and does not need to be specifically limited. However, the metering speed of the shell layer and the core layer, and the speed ratio between the spinneret and the drawing machine will affect the layer-by-layer stacking effect of the MXene nanosheets in the obtained functional fiber. Therefore, in the embodiments of the present invention, the metering speed ratio of the shell layer and the core layer during the wet spinning process is (1-5): 1, and the drawing speed ratio of the spinneret, the first drawing machine, and the second drawing machine is 1:1: (1-5).
[0032] The present invention adopts coaxial wet spinning to avoid the coagulation of incompatible components in the PVP solution and the loss of MXene nanosheets during the spinning process.
[0033] It should be noted that the wet spinning method used in the present invention is a conventional means in the art and is not specifically limited. The following only provides the operating steps as an example of wet spinning: the core-shell spinning solutions are respectively connected to different injection pumps, and injected into a coagulation bath through a coaxial spinning needle at different injection speeds to form nascent fibers; the nascent fibers pass through a drawing machine into a water washing bath to clean the coagulant attached to the fiber surface, and then the moisture is removed by slit heating and drying; the dried fibers are further subjected to dry heat stretching treatment to improve the strength of the fibers; and the fibers are collected into rolls by a winder.
[0034] For reference, the coagulation bath used in the wet spinning in this embodiment is a saturated anhydrous sodium sulfate solution.
[0035] The preparation method of MXene nanosheets is also a common technical means in the prior art to etch the aluminum layer in Ti3AlC2 using HF, and is not specifically limited. The preparation method given below is only an example: Ti3AlC2 selectively etches the aluminum layer in HCl / LiF solution, and after ultrasonic peeling of the aluminum layer, the supernatant is taken by centrifugation and freeze-dried.
[0036] In some preferred embodiments, collagen can be added to the shell spinning solution to improve the biocompatibility of the functional fiber, that is, polyvinyl pyrrolidone and collagen are dissolved in water to obtain the shell spinning solution.
[0037] The specific embodiments of the present invention are disclosed below to illustrate the functional fibers, their preparation and specific properties.
[0038] Example 1 Preparation of MXene dispersion: First, Ti3AlC2 is etched. 40 mL of 9 mol / L hydrochloric acid solution and 3.2 g of lithium fluoride are added as etchants to a polytetrafluoroethylene beaker and stirred in an ice-water bath for 10 min. 2 g of Ti3AlC2 powder is slowly added to the beaker in small amounts and multiple times, and then the mixed solution is stirred in a 45°C oil bath for 24 h to etch away the aluminum layer. After etching, the acid is washed by centrifugation at 3500 rpm with deionized water several times until the supernatant is close to neutral. The bottom precipitate is collected, an appropriate amount of deionized water is added, and ultrasonic vibration is performed under nitrogen protection for 1 hour. Finally, the solution is centrifuged at 3500 rpm for 45 min. After centrifugation, the supernatant is taken to obtain a single layer of Ti3C2T x MXene dispersion (hereinafter referred to as "MXene dispersion"), the digital photo of which is as follows Figure 1 As shown. Monolayer Ti3C2T in MXene dispersion x The microscopic morphology of MXene nanosheets is as follows Figure 2 As shown, from Figure 2 A clear lamellar structure can be observed, indicating that the preparation was successful. Figure 3 A single layer of Ti3C2T in MXene dispersion x The X-ray diffraction spectrum of MXene nanosheets shows that the MXene dispersion was successfully prepared.
[0039] Preparation of TA-MXene dispersion: The above dispersion was freeze-dried to obtain Ti3C2T x MXene nanosheets. Take 5 g of MXene nanosheets in deionized water, ultrasonically disperse for 30 min, then add the same mass of TA, use tris buffer to adjust the solution pH to 8, and magnetically stir for 12 h to obtain a dark green TA-MXene dispersion. The effect of the MXene dispersion after standing for 50 days is shown in the figure below. Figure 4 As shown. Figure 4 It can be seen that the water dispersibility of TA-MXene dispersion modified by TA is significantly improved, and the water stability is better.
[0040] Preparation of Col / PVP aqueous solution: Weigh 50 g of polyvinyl pyrrolidone particles and collagen powder respectively, add a certain amount of water in proportion and transfer to a container with a stirring device, stir at room temperature for 30 min, and after complete dissolution, a 10 wt% Col / PVP aqueous solution is obtained.
[0041] The TA-MXene dispersion was used as the core spinning solution, the Col / PVP solution was used as the shell spinning solution, and a coaxial spinning needle with an inner diameter of 22G and an outer diameter of 17G was used as the spinning head. The core and shell spinning solutions were injected into a coagulation bath of saturated anhydrous sodium sulfate solution at an injection rate of 7mL / h and 21mL / h, respectively, to obtain primary fibers. After the fibers were coagulated in the coagulation bath, they were transferred to a water washing bath through a drawing machine to remove the coagulant remaining on the fiber surface. The fibers were then subjected to slit heating drying and dry heat stretching treatment, and finally collected into rolls to obtain the finished fiber Col / PVP@TA-MXene.
[0042] Example 2 Preparation of MXene dispersion: First, Ti3AlC2 is etched. 40 mL of 9 mol / L hydrochloric acid solution and 3.2 g of lithium fluoride are added as etchants to a polytetrafluoroethylene beaker and stirred in an ice-water bath for 10 min. 2 g of Ti3AlC2 powder is slowly added to the beaker in small amounts and multiple times, and then the mixed solution is stirred in a 45°C oil bath for 24 h to etch away the aluminum layer. After etching, the acid is washed by centrifugation at 3500 rpm with deionized water several times until the supernatant is close to neutral. The bottom precipitate is collected, an appropriate amount of deionized water is added, and ultrasonic vibration is performed under nitrogen protection for 1 hour. Finally, the solution is centrifuged at 3500 rpm for 45 min. After centrifugation, the supernatant is taken to obtain a single layer of Ti3C2T x MXene dispersion.
[0043] Preparation of TA-MXene dispersion: After freeze-drying the above dispersion, MXene nanosheets were obtained. 9 g of MXene nanosheets were taken in deionized water, ultrasonically dispersed for 30 min, and then 1 g of TA was added. The pH value of the solution was adjusted to 8 using tris buffer, and magnetic stirring was performed for 12 h to obtain TA-MXene dispersion.
[0044] Preparation of Col / PVP aqueous solution: Weigh 50 g of polyvinyl pyrrolidone particles and collagen powder respectively, add a certain amount of water in proportion and transfer to a container with a stirring device, stir at room temperature for 30 min, and after complete dissolution, a 10 wt% Col / PVP aqueous solution is obtained.
[0045] The TA-MXene dispersion was used as the core spinning solution, the Col / PVP solution was used as the shell spinning solution, and a coaxial spinning needle with an inner diameter of 22G and an outer diameter of 17G was used as the spinning head. The core and shell spinning solutions were injected into a coagulation bath of saturated anhydrous sodium sulfate solution at an injection rate of 7 mL / h and 21 mL / h, respectively, to obtain primary fibers. After the fibers were coagulated in the coagulation bath, they were transferred to a water washing bath through a drawing machine to remove the coagulant remaining on the fiber surface. The fibers were then subjected to slit heating drying and dry heat stretching treatment, and finally collected into rolls to obtain the finished fiber Col / PVP@TA-MXene.
[0046] Example 3 Preparation of MXene dispersion: First, Ti3AlC2 is etched. 40 mL of 9 mol / L hydrochloric acid solution and 3.2 g of lithium fluoride are added as etchants to a polytetrafluoroethylene beaker and stirred in an ice-water bath for 10 min. 2 g of Ti3AlC2 powder is slowly added to the beaker in small amounts and multiple times, and then the mixed solution is stirred in a 45°C oil bath for 24 h to etch away the aluminum layer. After etching, the acid is washed by centrifugation at 3500 rpm with deionized water several times until the supernatant is close to neutral. The bottom precipitate is collected, an appropriate amount of deionized water is added, and ultrasonic vibration is performed under nitrogen protection for 1 hour. Finally, the solution is centrifuged at 3500 rpm for 45 min. After centrifugation, the supernatant is taken to obtain a single layer of Ti3C2T x MXene dispersion.
[0047] Preparation of TA-MXene dispersion: After freeze-drying the above dispersion, MXene nanosheets were obtained. 5 g of MXene nanosheets were taken in deionized water, ultrasonically dispersed for 30 min, and then 1 g of TA was added. The pH value of the solution was adjusted to 8 using tris buffer, and magnetic stirring was performed for 12 h to obtain TA-MXene dispersion.
[0048] Preparation of PVP aqueous solution: Weigh 50 g of polyvinyl pyrrolidone particles, add a certain amount of water in proportion and transfer to a container with a stirring device, stir at room temperature for 30 min, and after complete dissolution, a 10 wt% PVP aqueous solution is obtained.
[0049] The TA-MXene dispersion was used as the core spinning solution, the PVP solution was used as the shell spinning solution, and a coaxial spinning needle with an inner diameter of 22G and an outer diameter of 17G was used as the spinning head. The core and shell spinning solutions were injected into a coagulation bath of saturated anhydrous sodium sulfate solution at an injection rate of 7 mL / h and 21 mL / h, respectively, to obtain primary fibers. After the fibers were coagulated in the coagulation bath, they were transferred to a water washing bath through a drawing machine to remove the coagulant remaining on the fiber surface. The fibers were then subjected to slit heating drying and dry heat stretching treatment, and finally collected into rolls to obtain the finished fiber PVP@TA-MXene.
[0050] Comparative Example 1 Compared with Example 1, the difference is that TA is not used to encapsulate the MXene nanosheets, as follows: Preparation of MXene dispersion: First, Ti3AlC2 is etched. 40 mL of 9 mol / L hydrochloric acid solution and 3.2 g of lithium fluoride are added as etchants to a polytetrafluoroethylene beaker and stirred in an ice-water bath for 10 min. 2 g of Ti3AlC2 powder is slowly added to the beaker in small amounts and multiple times, and then the mixed solution is stirred in a 45°C oil bath for 24 h to etch away the aluminum layer. After etching, the acid is washed by centrifugation at 3500 rpm with deionized water several times until the supernatant is close to neutral. The bottom precipitate is collected, an appropriate amount of deionized water is added, and ultrasonic vibration is performed under nitrogen protection for 1 hour. Finally, the solution is centrifuged at 3500 rpm for 45 min. After centrifugation, the supernatant is taken to obtain a single layer of Ti3C2T x MXene dispersion.
[0051] Preparation of Col / PVP aqueous solution: Weigh 50 g of polyvinyl pyrrolidone particles and collagen powder respectively, add a certain amount of water in proportion and transfer to a container with a stirring device, stir at room temperature for 30 min, and after complete dissolution, a 10 wt% Col / PVP aqueous solution is obtained.
[0052] The MXene dispersion was used as the core spinning solution, the Col / PVP solution was used as the shell spinning solution, and a coaxial spinning needle with an inner diameter of 22G and an outer diameter of 17G was used as the spinning head. The core and shell spinning solutions were injected into a coagulation bath of saturated anhydrous sodium sulfate solution at an injection rate of 7 mL / h and 21 mL / h, respectively, to obtain primary fibers. After the fibers were coagulated in the coagulation bath, they were transferred to a water washing bath through a drawing machine to remove the coagulant remaining on the fiber surface. The fibers were then subjected to slit heating drying and dry heat stretching treatment, and finally collected into rolls to obtain the finished fiber Col / PVP@MXene.
[0053] Comparative Example 2 Compared with Example 1, the difference is that the metering speed of the core layer and the shell layer has changed, as follows: Preparation of MXene dispersion: First, Ti3AlC2 is etched. 40 mL of 9 mol / L hydrochloric acid solution and 3.2 g of lithium fluoride are added as etchants to a polytetrafluoroethylene beaker and stirred in an ice-water bath for 10 min. 2 g of Ti3AlC2 powder is slowly added to the beaker in small amounts and multiple times, and then the mixed solution is stirred in a 45°C oil bath for 24 h to etch away the aluminum layer. After etching, the acid is washed by centrifugation at 3500 rpm with deionized water several times until the supernatant is close to neutral. The bottom precipitate is collected, an appropriate amount of deionized water is added, and ultrasonic vibration is performed under nitrogen protection for 1 hour. Finally, the solution is centrifuged at 3500 rpm for 45 min. After centrifugation, the supernatant is taken to obtain a single layer of Ti3C2T x MXene dispersion.
[0054] Preparation of TA-MXene dispersion: After freeze-drying the above dispersion, MXene nanosheets were obtained. 5 g of MXene nanosheets were taken in deionized water and ultrasonically dispersed for 30 min, and then the same mass of TA was added. The pH value of the solution was adjusted to 8 using tris buffer and magnetically stirred for 12 h to obtain a dark green TA-MXene dispersion.
[0055] Preparation of Col / PVP aqueous solution: Weigh 50 g of polyvinyl pyrrolidone particles and collagen powder respectively, add a certain amount of water in proportion and transfer to a container with a stirring device, stir at room temperature for 30 min, and after complete dissolution, a 10 wt% Col / PVP aqueous solution is obtained.
[0056] The TA-MXene dispersion was used as the core spinning solution, the Col / PVP solution was used as the shell spinning solution, and a coaxial spinning needle with an inner diameter of 22G and an outer diameter of 17G was used as the spinning head. The core and shell spinning solutions were injected into a coagulation bath of saturated anhydrous sodium sulfate solution at injection speeds of 14 mL / h and 7 mL / h, respectively, to obtain primary fibers. After the fibers were coagulated in the coagulation bath, they were transferred to a water washing bath through a drawing machine to remove the coagulant remaining on the fiber surface. The fibers were then subjected to slit heating drying and dry heat stretching treatments, and finally collected into rolls to obtain the finished fiber Col / PVP@TA-MXene.
[0057] Test example The functional fibers prepared in Example 1 and Comparative Examples 1-2 were subjected to various performance tests, as follows: The morphology of the Col / PVP@TA-MXene fiber in Example 1 was observed by field emission scanning electron microscopy (SEM). The surface (ab) and cross-section (cd) microscopic morphologies are shown in Figure 2. Figure 5 As shown, from the cross-sectional SEM image, it can be observed that the TA-MXene nanosheets in the core layer are stacked layer by layer and arranged along the fiber axis.
[0058] The orientation of the coaxial fibers obtained in Example 1 and Comparative Examples 1-2 was tested by small angle X-ray diffraction (SAXS). Figure 6 As shown. After calculation of Example 1 ( Figure 6 a) can reach a coaxial fiber orientation factor f of 0.874, which is much larger than that of comparative example 1-2 ( Figure 6 bc) The obtained fibers prove that the fibers have good structural orientation.
[0059] The fibers in Example 1 and Comparative Examples 1-2 were washed with water, alkali and acid respectively, and then the resistance change of the fibers was tested using an electrochemical workstation. The results are as follows: Figure 7 The results show that the resistance of the Col / PVP@TA-MXene fiber modified by TA in Example 1 does not change much, proving that it has good environmental stability.
[0060] The functionality of the fiber obtained in Example 1 was tested using the IT mode of the electrochemical workstation. Figure 8 As shown in the figure, the fiber can respond to different human behaviors (such as bending fingers, running and walking, etc.), proving that the fiber has good sensing function. For example, bending and straightening fingers will cause the resistance of the fiber to change, and the change in current will be fed back through the electrochemical workstation, thus obtaining Figure 8 That is, the electrical signal changes once the finger bends and straightens, and the cycle repeats itself.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. Highly ordered functional fibers, characterized in that It is a coaxial fiber with a core layer and a shell layer prepared by wet spinning. The core layer is a composite material obtained by self-assembly of tannic acid-encapsulated MXene nanosheets, which has a layer-by-layer oriented structure, and the shell layer is polyvinyl pyrrolidone.
2. The highly ordered functional fiber according to claim 1, characterized in that: The mass ratio of the tannic acid to the MXene nanosheets is 1:(1-9).
3. The highly ordered functional fiber according to claim 1 or 2, characterized in that: The shell also contains collagen.
4. The highly ordered functional fiber according to claim 3, characterized in that: The mass ratio of the collagen to polyvinyl pyrrolidone is 1:(1-5).
5. The method for preparing the highly ordered functional fiber according to any one of claims 1 to 4, characterized in that: Include: The MXene nanosheets were dispersed in deionized water, tannic acid was added, and magnetic stirring was performed at pH 7-10 for 1-12 h to obtain a core layer spinning solution; Dissolving polyvinyl pyrrolidone in water to obtain a shell spinning solution; The core layer spinning solution and the shell layer spinning solution are used to prepare coaxial fibers by wet spinning.
6. The preparation method according to claim 5, characterized in that: The preparation method of MXene nanosheets is as follows: Ti3AlC2 selectively etches the aluminum layer in HCl / LiF solution, ultrasonically peels off the aluminum layer, centrifuges to obtain the supernatant, and freeze-dries the supernatant.
7. The preparation method according to claim 5 or 6, characterized in that: The shell spinning solution is obtained by dissolving polyvinyl pyrrolidone and collagen in water.
8. The preparation method according to claim 5, characterized in that: The coagulation bath used in wet spinning is a saturated anhydrous sodium sulfate solution.
9. The preparation method according to claim 5, characterized in that: The metering speed ratio of the shell layer and the core layer during the wet spinning process is (1-5):
1.
10. The preparation method according to claim 5, characterized in that: During the wet spinning process, the drawing speed ratio of the spinneret, the first drawing machine, and the second drawing machine is 1:1:(1-5).
Citation Information
Patent Citations
Fiber and preparation method thereof
CN114438618A
Thermal electric gel fiber with skin-core structure as well as preparation method and application of thermal electric gel fiber
CN117210961A
Preparation method of calcium phosphate bone cement for promoting mechanical enhancement of bony grove structure
CN117838927A
High-barrier strong-corrosion-resistance composite coating as well as preparation method and application thereof
CN118772740A
Cited By
High-modulus MXene-based fiber and preparation method thereof
CN121451329A